2013
DOI: 10.1016/j.healthplace.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Is walkability associated with a lower cardiometabolic risk?

Abstract: Walkability of residential environments has been associated with more walking. Given the health benefits of walking, it is expected that people living in locations with higher measured walkability should have a lower risk of cardiometabolic diseases. This study tested the hypothesis that higher walkability was associated with a lower cardiometabolic risk (CMR) for two administrative spatial units and three road buffers. Data were from the North West Adelaide Health Study first wave of data collected between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 52 publications
2
43
0
2
Order By: Relevance
“…Similarly to our study, other investigators have corresponding results [31]. For instance, Coffee et al [26] used geographic information system to test the hypothesis that higher walkability index was associated with a lower cardiometabolic risk (CMR) among Australian adults. Their study revealed that a lower CMR score (including hypertension) was associated with higher walkability index.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly to our study, other investigators have corresponding results [31]. For instance, Coffee et al [26] used geographic information system to test the hypothesis that higher walkability index was associated with a lower cardiometabolic risk (CMR) among Australian adults. Their study revealed that a lower CMR score (including hypertension) was associated with higher walkability index.…”
Section: Discussionsupporting
confidence: 79%
“…There is very scant literature on this field. It has been suggested that research should move beyond evaluating the relationships between the built environment and walking, to chronic disease risk factors and outcomes that relate to walkability as well as more specific characteristics of the built environment [26]. Similarly to our study, other investigators have corresponding results [31].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, it is important to create high-walkability and supportive environments to promote public health. 24 Urban development is also an important factor in walkable neighborhoods. To increase the WI, the governments should improve resident density, LUM, SC, safety, and socioeconomic status in the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have linked sedentary lifestyles and unhealthy eating patterns to obesity in LMICs [11], as well as the deleterious effects to health from low-quality education [12], poor built environment [13] and social interaction [14]. Empirical research taking the SDH as its lens has helped to discredit the characterisation of NCDs as diseases of affluence, yet its impact on policy is less definite.…”
Section: Introductionmentioning
confidence: 99%